Foreign Exchange Risk Management Strategies Through Financial Engineering: An Analysis of Forex Exposure, Transaction Exposure, Economic Exposure, and Translation Exposure - Syahwildan, Muhammad; Marlina, Ellin; Zendrato, Erni Putri Setia; Ashari, Widya Jeihan; Putri, Tania Melani; Wardani, Alfina Ayu (Indonesian Journal of Contemporary Multidisciplinary Research, 2025)
This study aims to develop foreign exchange risk management strategies through financial engineering, focusing on Forex Exposure, Transaction Exposure, Economic Exposure, and Translation Exposure. Using a quantitative approach and historical data analysis, it examines the impact of exchange rate fluctuations on corporate financial performance. A case study on an international trading company identifies risk mitigation strategies, such as the use of financial derivatives. The findings indicate that effective risk management strategies can reduce profit volatility by up to 15%. This research presents a comprehensive model for foreign exchange risk management, contributing to financial literature and business practices.